2019
DOI: 10.32794/mr11250026
|View full text |Cite
|
Sign up to set email alerts
|

Clock genes and the role of melatonin in cancer cells: an overview

Abstract: Circadian rhythms control most biological processes in every organism and their disruption or an aberrant function in the expression of clock genes are associated with a number of cancers including some hormone-dependent and independent cancers. The processes involved in carcinogenesis and tumor progression are complex, but understanding the daily profiles of the core clock genes and their clock-controlled genes is essential to evaluate specifically the molecular program of the cancer phenotype; this may be he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Moreover, melatonin, the secretory product of pineal gland, has also been recently reported to promote the synthesis of acetyl-CoA from pyruvate by inhibiting PDK in breast cancer models [160]. The inhibitory effect of melatonin on PDK not only reverses the Warburg effect, reduces tumor mass, and improves the sensitivity of tumor cells to chemoradiotherapy [160,161], it also leads to a circadian rhythm of glucose metabolism in these cancer cells [162,163].…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…Moreover, melatonin, the secretory product of pineal gland, has also been recently reported to promote the synthesis of acetyl-CoA from pyruvate by inhibiting PDK in breast cancer models [160]. The inhibitory effect of melatonin on PDK not only reverses the Warburg effect, reduces tumor mass, and improves the sensitivity of tumor cells to chemoradiotherapy [160,161], it also leads to a circadian rhythm of glucose metabolism in these cancer cells [162,163].…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…A number of epidemiological studies have shown the clinical effectiveness of melatonin in reducing both the risk of developing PCa and its aggressiveness [1,14]. In vitro/in vivo studies demonstrate various mechanisms of inhibition of tumor proliferation of prostate adenocarcinoma cells both by enhancing apoptosis and cytoreduction, and by reducing tumor potential and angiogenesis [6,7,15,16]. Of particular interest are the works demonstrating positive results of melatonin use in treatment of castrate-resistant metastatic PCa, when the possibilities of most available drugs have already been exhausted.…”
Section: Research Papermentioning
confidence: 99%
“…A plethora of recent studies has documented that melatonin synchronizes the clockwork machinery in healthy and damaged cells, either up or downregulating specific clock genes to maintain optimal physiology [29][30][31]. Through its multiple actions, melatonin works as a circadian regulator, natural antioxidant, and anti-inflammatory and oncostatic agent, like many other functions [32][33][34].…”
Section: The Uterine Biological Rhythm As a Target For Melatonin's Acmentioning
confidence: 99%
“…Melatonin receptors are formed by seven transmembrane domains coupled to high-affinity G protein, termed melatonin receptor 1 (MT1) (also called MTNR1A or Mel1a), MT2 (also called MTNR1B or Mel1b), and MT3 (identified as quinone reductase II enzyme); they often act as homo or heterodimers to reduce the levels of cAMP and cGMP thereby increasing phosphorylation of other proteins [35]. Due to its amphiphilicity, melatonin crosses the cell membrane thus interacting with intracellular molecules via different signaling pathways; these include scavenger functions, binding to calmodulin, and many other molecules [31]. The statement that melatonin binds to RORα and RORγ has been previously investigated and they found a lack of effect of melatonin and its derivatives on RORα and RORγ activities, thereby showing by docking analyses that these nuclear receptors have no high-affinity for melatonin [36,37].…”
Section: The Uterine Biological Rhythm As a Target For Melatonin's Acmentioning
confidence: 99%